2008
DOI: 10.4142/jvs.2008.9.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxine induced neuropathy by subcutaneous administration in dogs

Abstract: To construct a sensory neuropathy model, excess pyridoxine (150 mg/kg s.i.d.) was injected subcutaneously in dogs over a period of 7 days. During the administrations period, the dogs experienced body weight reduction and proprioceptive loss involving the hindquarters. After pyridoxine administration was completed, electrophysiological recordings showed that the M wave remained at a normal state, but the H-reflex of the treated dogs disappeared at 7 days. The dorsal funiculus of L4 was disrupted irregularly in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 12 publications
3
34
1
Order By: Relevance
“…Electrophysiological recordings taken during peripheral nerve stimulation in the experimental group were consistent with selective toxicity to sensory, but not motor nerve function. We also confirmed that this procedure was suitable in dog studies with PDX induced sensory neuropathy [7].…”
Section: Discussionsupporting
confidence: 77%
“…Electrophysiological recordings taken during peripheral nerve stimulation in the experimental group were consistent with selective toxicity to sensory, but not motor nerve function. We also confirmed that this procedure was suitable in dog studies with PDX induced sensory neuropathy [7].…”
Section: Discussionsupporting
confidence: 77%
“…Such leakage does not appear to occur in hypophosphatasia. High doses of pyridoxine cause neuropathy in rats (Callizot et al 2001), dogs (Chung et al 2008) and humans (Gdynia et al 2008). There is one case report of pyridoxine responsive seizures in an infant whose mother consumed 80 mg pyridoxine/d during her pregnancy (South 1999b).…”
Section: Vitamin B-6 and Seizuresmentioning
confidence: 99%
“…30) In rodent models, intoxication with pyridoxine causes axonal degeneration in the dorsal roots and the central projections of the same neurons in the dorsal horn of the spinal cord, while sparing the ventral roots. 31) The effect is dose dependent; at low dosages, the resultant damage occurs predominantly in the distal axon, while with progressively increasing dosages pathological abnormalities are produced in the primary neurons in the DRG.…”
Section: Anmentioning
confidence: 99%